Intracranial pressure, cerebral perfusion pressure and cerebral compliance monitoring and their relationship amongst adult severe head injury - Nujaimin, Udin (2008)
The study is to observe the correlation between intracranial physiological parameters namely intracranial pressure (ICP), cerebral perfusion pressure (CPP) and cerebral compliance in adult severe head injured patients. In addition the relationship of the above parameters with post operative computed tomography scan and other potential clinical, non clinical factors and outcome were also analyzed.This is a prospective cohort study on severe head injured patients with Glasgow Coma Score of eight and below. The patients were admitted into Neuroscience Intensive Care Unit for monitoring of intracranial and extracranial physiological parameters after evacuation of mass lesion. We excluded patients with bilateral fixed and dilated pupil, those who suffered from severe injury not expected to live longer than 24 hours, those with bleeding diathesis, those whose follow up was not possible or those with significant brain stem involvement. All patients were treated with standard protocols and guidelines in the management of severe head injury. These patients were monitored continuously until the parameters were normal and stabilized or death. Post operative computed tomography was obtained within 48 hours after surgical evacuation of mass lesion or earlier if intracranial hypertension was refractory. Outcomes of the patients at first and sixth month after the injury were assessed using Glasgow Outcome Scale.The study included 30 patients with 24 males and 6 females, between 13 and 65 years of age who were admitted with severe head injury. We demonstrated higher CPP and compliance values were obtained whenever the ICP was maintained at 20 mmHg or lower, while reduced CPP and compliance value once the ICP was elevated above 20 mmHg following surgery to remove the mass lesion in severe head injured patients, p value = 0.001 and 0.030 respectively. The similar findings were demonstrated when cerebral compliance was measured using PVI, p value < 0.001. There was a statistically significant correlation between CPP and compliance as well as CPP and PVI at ICP above 20 mmHg, p value < 0. 001 . Our study also revealed higher ICP and lower compliance and PVI when the CPP was below 60 mmHg. The ICP reduced (p value < 0.001) and both compliance (p value = 0.002) as well as PVI (p value < 0.001) improved when the CPP was preserved above 60 mmHg. Post operatively, our study revealed significant relationship between ICP and CPP with states of basal cistern (p value = 0.001 and 0.022) as well as ICP with Marshall Classification (p value < 0.001). However we fai led to demonstrate significant relation between compliance with post operative CT scan findings even though higher compliance value was observed when the basal cistern was opened, less midline shift and Marshall I or ll. We also found an association between preoperative GCS with ICP and type of operation with compliance value which may help in the management plan of severe head injured patients,p value = 0.006 and 0.033 respectively. Age, preoperative GCS, pupil equality and reactivity, basal cistern, post operative CT scan edema and ICP were associated with the outcome of the patients at one month aftersevere head injury, p value< 0.050, although we only found pupil equality and reactivity (p value = 0.025) and barely ICP (p value = 0.057) as independent outcome predictors. Larger sample size is required to demonstrate the validity of other parameters as an independent predictor. Lastly the invasive procedure such as insertion of ICP monitoring is not without catastrophic complication.There were correlation between ICP, CPP and cerebral compliance as long as the cerebral autoregulation remained intact However no significant relation was observed between these intracranial parameters with the patient's outcome. Other than that, the findings of post operative CT scan obtained after evacuation of mass lesion may help in predicting the intracranial pressure.